Self-medication prevalence in a Portuguese Urban Area (Revista Brasileira de Ciências Farmacêuticas, 2004)
To determine the prevalence of self-medication in a Portuguese urban population, a cross-sectional study was carried out in Lisbon (11 pharmacies) and Oporto (15 pharmacies). Data collection took place between November 1995 and September 1996, during 6 periods of 10 days each. The overall prevalence of self-medication found was 26,2%. Statistical significant differences were found between self-medication prevalence according to sex, age, educational level and professional status. Fifty percent of the individuals who have used drugs in self-medication did so with the pharmacist advice. The most frequent therapeutic groups used in self-medication were cough and cold preparations (23%) and analgesics (13,6%). Analysing each group separately, statistical significant differences for sex and age were found according to the variable self-medication.